Hepatitis B virus infection in a population exposed to occupational hazards: firefighters of a metropolitan region in central Brazil - Contrera-Moreno,Luciana (2012)
INTRODUCTION: By the nature of their activities, firefighters are exposed to a high risk of contracting hepatitis B virus (HBV) as most of the Fire Brigade occurrences in Campo Grande, State of Mato Grosso do Sul (MS), Brazil, are related to the rescue of victims of traffic accidents and the transportation of clinical and psychiatric emergencies. The aim of this study was to investigate the seroepidemiological profile of HBV infection in firefighters from the City of Campo Grande, central Brazil. METHODS: The research involved 308 firefighters. After giving written consent, they were interviewed and blood was collected for the detection of HBsAg, anti-HBs and total anti-HBc of enzyme-linked immunosorbent assays (ELISA). RESULTS: The participants had an average of 36.4 years of age (SD ± 6.5), being 89.9% male. Blood tests revealed 6.5% of seropositivity for hepatitis B (HB) infection (n=20), and 1% for HbsAg. Isolated anti-HBs markers, indicative of vaccine immunity, were found in 66.9% of the participants and 28.2% were susceptible to infection. With regard to risk factors for HB infection, multivariate regression analysis showed a statistically significant association with length of service; and prevalence was higher in individuals with over 20 years of service. CONCLUSIONS: The prevalence of HB found among the firefighters was low and length of time in the profession was found to be a risk factor. Non-occupational risk factors did not influence the occurrence of HB infection in the population studied.